Bitumen Coating as a Tool for Improving the Porosity and Chemical Stability of Simulated Cement-Waste Forms. (29th November 2012) - Saleh, H. M.
Abstract : Coating of simulated cement-based waste form was investigated by performing physical and chemical experimental tests. Moreover, X-ray diffraction, Fourier transform infrared spectroscopy, and electron microscope examination were applied on coated and noncoated simulated waste forms. Experimental results indicated that coating process improved the characterizations of cement-based waste form such as porosity and leachability. Diffusion coefficients and leach indecies of coated specimens were calculated and showed acceptable values. It could be stated that by coating cemented-waste form by bitumen emulsion, the radioactive contaminants were isolated, thus reducing the back release to surrounding environment during flooding by groundwater and consequently, saving the environment.